UNDERSTANDING BY DESIGN (UBD) FOR THE PHYSICS LEARNING ABOUT PARABOLIC MOTION - Kuntari, Fransiska Retno; Rondonuwu, Ferdy Semuel; Sudjito, Debora Natalia (Universitas Negeri Surabaya, 2019)
In general, in preparing the lesson, teachers determine some components namely learning objectives, procedures, and evaluation and assessment instruments. Several problems in Physics learning on Parabolic Motion indicate possible flaws from the three components in designing the lesson. Understanding by Design (UbD) is applied as one of the alternative strategies to improve the lesson quality by considering the learning objectives, procedures, and evaluation by reversing the design, namely proposing the objectives first, evaluations as the second, and lesson steps as the last step. This is a qualitative research intended to construct an alternative design of Physics learning on Parabolic Motion using UbD. The initial Physics learning design was reviewed and analyzed by experts and revised until the final design. Understanding by Design (UbD) could be used as an alternative design construction as it helps teachers to relate the three main components, namely learning objectives, evaluations, and steps so it eased the students understand the materials comprehensively and obtain maximum score. Despite the development of current materials needs more improvement, Understanding by Design (UbD) can applied for many materials.